Pengaruh Pola Asuh Terhadap Kepercayaan Diri Anak Tuna Daksa (Disabilitas Fisik) - Amelia Putri Nirmala (Journal on Education, 2024)
The objectives of this research include: describing in a descriptive way the parenting patterns of parents who have children with physical impairments, explaining the factors that influence the self-confidence of children with physical impairments and explaining the impact of the parenting patterns implemented by parents. The method in this research uses descriptive qualitative. Data collection techniques use observation and interviews and then analyzed using theory or other literature sources. The technique for selecting research respondents uses purposive sampling technique. Respondents in this study were: parents who have disabled children, parents aged 25-40 years and parents whose children are studying at junior high school or high school. The number of responses in this study were 3 parents who had children with physical impairments. The results of this study explain that the parenting style applied by parents can influence the self-confidence of children with physical impairments. Subject A and subject B received an authoritarian parenting style while subject C received a democratic parenting style. The parenting habits implemented by parents have an impact on the child's personality, which causes one subject to have different self-confidence.